Mono Economy Syndrome of Nigeria: Reposition of Manufacturing Sector for Sustainable Diversification and Development - Idowu, S. Samuel (Research Nepal Journal of Development Studies, 2020)
The study examines Nigeria challenge of the mono-culture economy due to an overreliance on oil, and coupled with the threat been stranded arising from the global campaign and signed Paris agreement in 2015 is an economic risk that could jeopardize her economic development. Answers to why the manufacturing sector has occupied a peripheral position in the Nigeria’s economic development aspiration question alongside the overarching goal of articulating pragmatic mediums and approaches for revamping the manufacturing industry from the encumbrances hindering its full capacity functioning. This research was undertaken to examine the manufacturing sector as an alternative to Nigeria’s petroleum dependence economy by dissecting its problems and how-to repositioning it for a viable diversification. The ex-post facto research method was adopted using impeccable secondary data sources. Insecurity and poor political governance were among other impediments to the manufacturing optimum performance, and strengthening the political institution for an all-inclusive government, amongst others, is proffered as panacea.